2017
DOI: 10.1016/j.gie.2017.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal dilation with either bougie or balloon technique as a treatment for eosinophilic esophagitis: a systematic review and meta-analysis

Abstract: Background and Aims Esophageal dilation is a now recognized to be an important therapeutic modality in eosinophilic esophagitis (EoE). We aimed to evaluate the safety of esophageal dilation in EoE, especially regarding perforation risk, and to examine perforation risk by dilator type. Methods We conducted a systematic review of the published literature from January 1, 1950 to June 30, 2016 using Pubmed, EMBASE, and Web of Science. Studies were included if they described patients with EoE who underwent esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 63 publications
2
55
0
5
Order By: Relevance
“…84 While dilation itself does not impact the underlying EoE disease process, 131 it immediately increases the caliber of the esophagus and leads to symptomatic improvement that may be long lasting. 16,132 In contrast, if a patient has a severe persistent stricture, they will remain symptomatic even if esophageal eosinophilia has resolved with antiinflammatory treatment. If inflammation persists at deeper esophageal levels such as the submucosa or muscularis propria, it has been recently shown that this could explain persistent symptoms despite normalization of mucosal biopsies 77 ; decreased esophageal compliance or unrecognized esophageal narrowing might provide a similar explanation.…”
Section: Comparativementioning
confidence: 99%
See 1 more Smart Citation
“…84 While dilation itself does not impact the underlying EoE disease process, 131 it immediately increases the caliber of the esophagus and leads to symptomatic improvement that may be long lasting. 16,132 In contrast, if a patient has a severe persistent stricture, they will remain symptomatic even if esophageal eosinophilia has resolved with antiinflammatory treatment. If inflammation persists at deeper esophageal levels such as the submucosa or muscularis propria, it has been recently shown that this could explain persistent symptoms despite normalization of mucosal biopsies 77 ; decreased esophageal compliance or unrecognized esophageal narrowing might provide a similar explanation.…”
Section: Comparativementioning
confidence: 99%
“…[8][9][10][11] After diagnosis, treatment modalities can include proton pump inhibitors, dietary elimination, swallowed or "topical" corticosteroids, and esophageal dilation when strictures are present. [12][13][14][15][16][17] With the quickly expanding knowledge of EoE pathogenesis, 18 novel treatment modalities including biologics and small molecules are also under development. 19,20 While the diagnosis and initial treatment of EoE are becoming more standardized, there are still major gaps in knowledge related to measuring treatment response.…”
mentioning
confidence: 99%
“…Unmittelbar postprozedurale Schmerzen wurden von 75 % der Pateinten berichtet (bei Entlassung nur noch 2 %). Eine weitere aktuelle Metaanalyse mit insgesamt 37 Studien, 977 Patienten und 2034 Dilatationen [115] kommt zu ähnlichen Ergebnissen, wobei die Komplikationsraten über die Zeit abzunehmen scheinen (vor 2009: 0,41 %, nach 2009: 0,03 %).…”
Section: Endoskopische Therapieunclassified
“…3 While still a rare disease, EoE has become more common, with an outsized burden-of-disease, estimated at more than $1 billion annually in health care-related costs. 4 Treatment of EoE involves targeting esophageal inflammation and, in patients with the fibrostenotic phenotype of EoE, addressing esophageal narrowing or strictures with dilation, 5 with the goal of achieving clinical remission of symptoms, improvement of endoscopic findings, and histologic normalization. [6][7][8][9] There are several pharmacologic treatment options for the esophageal mucosal inflammation, including the use of proton pump inhibitors, which restore mucosal integrity and block the expression of the cytokine eotaxin-3, [10][11][12][13] swallowed topical steroids, ideally in an esophageal-specific preparation, 14,15 and novel biologics that target proinflammatory mediators such as IL-5, 16,17 IL-13, 18,19 and IL-4, 20 which have shown promise in initial investigations.…”
Section: Introductionmentioning
confidence: 99%